Case report: Spiller syndrome initially mimicking vestibular neuritis - Wang, Huiyuan; Shi, Tianming; Shang, Yafei; Chen, Xinyi; Xu, Jie; Geng, Yu (Frontiers in Neurology, 2023)
Spiller syndrome is a rare subtype of medial medullary infarction (MMI). Herein, we report on a patient with progressing stroke who presented with the initial features of acute peripheral vestibulopathy and MMI (Spiller syndrome), as confirmed by magnetic resonance imaging (MRI). A 42-year-old man experienced acute persistent vertigo with nausea, vomiting, and severe gait instability for 6 h before presenting to the emergency department. He exhibited spontaneous right-beating horizontal-torsional nystagmus that intensified on rightward gaze. The patient fell to the left side during the Romberg test. Cranial computed tomography (CT) performed immediately upon admission did not provide evidence for ischemia or hemorrhage of the brainstem and cerebellum; however, the symptoms underwent exacerbation 4 h after admission, manifesting as left-sided limb weakness and dysarthria, without dysphagia. Furthermore, bedside examination revealed difficulty in extending the tongue to the right, positive left Babinski's sign, and abnormal vibration and position sense in the paralyzed limb. Head impulse test recording revealed a normal gain in the vestibulo-ocular reflex, and numerous consistent covert corrective saccades were captured upon turning the head to the left side. Cranial MRI depicted an acute infarct confined to the right side of the medial medulla, which met the diagnostic criteria for Spiller syndrome. Our study underscores the importance of considering the possibility of a nucleus prepositus hypoglossi lesion even if the signs and symptoms support the diagnosis of peripheral lesions in patients with acute vestibular syndrome exhibiting vascular risk factors.